Unveiling the physiological impact of ESCRT-dependent autophagosome closure by targeting the VPS37A ubiquitin E2 variant-like domain - Kouta Hamamoto; Xinwen Liang; Ayako Ito; Matthew Lanza; Van Bui; Jiawen Zhang; David M. Opozda; Tatsuya Hattori; Longgui Chen; David Haddock; Fumiaki Imamura; Hong-Gang Wang; et al. (Cell Reports)
Summary: Macroautophagy (autophagy) involves the formation of phagophores that mature into autophagosomes. The impact of inhibiting autophagosome closure remains unclear. Here, we report the generation and analysis of mice with impaired autophagosome closure by targeting the ubiquitin E2 variant-like (UEVL) β strands of the endosomal sorting complex required for transport (ESCRT) I subunit VPS37A. The VPS37A UEVL mutation (Δ43–139) impairs bulk autophagic flux without disrupting ESCRT-I complex assembly and endosomal function. Homozygous mutant mice exhibit signs of autophagy impairment, including p62/SQSTM1 and ubiquitinated protein accumulation, neuronal dysfunction, growth retardation, antioxidant gene upregulation, and tissue abnormalities. However, about half of the mutant neonates survive to adulthood without severe liver injury. LC3 proximity proteomics reveals that the VPS37A UEVL mutation leads to active TANK-binding kinase 1 (TBK1) accumulation on phagophores, resulting in increased p62 phosphorylation and inclusion formation. These findings reveal a previously unappreciated role of LC3-conjugated phagophores in facilitating protein aggregation and sequestration, potentially alleviating proteotoxicity.